STUDI KRITIS BAHAN AJAR PAI DALAM MATERI MENJAUHI PERGAULAN BEBAS DAN PERBUATAN ZINA UNTUK MELINDUNGI HARKAT DAN MARTABAT MANUSIA KELAS X SMA KOTA SUKABUMI - Amirulloh; Siti Qomariyah; Hoerul Anwar; Agus Mulyadi; Opik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to critically analyze Islamic Religious Education (PAI) teaching materials on the topic of Avoiding Free Association and Adultery to Protect Human Dignity for grade X students at SMA Kota Sukabumi. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results show that the teaching materials are generally well-structured and include essential components of learning, namely objectives, materials, methods, evaluation, and learning resources. The learning objectives have covered cognitive, affective, and psychomotor domains, but they still need to be refined to become more specific and measurable. The learning materials are relevant and systematically arranged; however, they require further contextualization, especially related to adolescents' lives in the digital era, as well as the development of higher-order thinking skills. The teaching methods are varied but still tend to be teacher-centered and not fully experience-based. The evaluation has covered multiple aspects, but it needs to be more authentic and supported by clear assessment rubrics. Learning resources are appropriate but need to be expanded by utilizing digital media and real-life environments. In conclusion, the PAI teaching materials have met basic educational standards; however, they still require development to become more contextual, applicable, and innovative in order to foster students who not only understand Islamic teachings theoretically but also apply them in daily life.